'You have been punished in prison. And then when you are released, you are punished for life': Post-incarceration barriers for women in Ukraine. (May 2022) - Korzh, Alla
Formerly incarcerated women face multidimensional barriers post-release, ranging from individual, relational, institutional, to systemic. Drawing on the conceptual framework of interlocking barriers facing formerly incarcerated women, this qualitative case study set in one minimum-security prison in Ukraine with 21 interviewed women, four teachers, and eight staff demonstrates that interlocking systemic barriers cemented in Ukrainian society complicate formerly incarcerated women's integration in society and may set them up for failure and recidivism. The study illuminates how the absence of housing, employment and discrimination, stigma, inadequate support system, lack of economic and cultural capital to pursue further education, and health challenges confronting incarcerated women post-release disadvantage the already vulnerable population in Ukraine. The findings of this study contribute to the field of sociology by highlighting the interlocking barriers confronting women post-incarceration and elucidating a gendered approach to understanding women's reentry experiences in Ukraine.